2019
DOI: 10.16993/sjdr.550
|View full text |Cite
|
Sign up to set email alerts
|

Work and Invisible Disabilities: Practices, Experiences and Understandings of (Non)Disclosure

Abstract: Invisible disabilities involve dilemmas that differentiate them from visible disabilities. However, little is known about the situation persons with invisible disabilities face at work, as empirical studies are scarce. The present article contributes in-depth knowledge of practices, experiences and understandings that affect the work situation for people with invisible disabilities in a Swedish context. The article draws on qualitative, in-depth interviews with 10 persons with invisible disabilities and seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 34 publications
1
18
0
2
Order By: Relevance
“…Currently, there are few studies examining workplace disclosure and support from an organizational standpoint [ 31 , 36 , 37 ]. This perspective is critical in addressing support gaps, understanding the interplay of key stakeholders, and in identifying new directions that can enable workers with episodic disabilities to better sustain employment or return to work.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are few studies examining workplace disclosure and support from an organizational standpoint [ 31 , 36 , 37 ]. This perspective is critical in addressing support gaps, understanding the interplay of key stakeholders, and in identifying new directions that can enable workers with episodic disabilities to better sustain employment or return to work.…”
Section: Introductionmentioning
confidence: 99%
“…Although none of the participants described any dilemmas regarding disclosure, the additional cases revealing that openness can have repercussions underscore the importance of questioning disclosure as a norm in return-to-work. A previous study found that while employer representatives framed disclosure as a valued practise leading to greater understanding and improved psychosocial work environment, employees experienced it as an “uncertain balancing act” (Norstedt, 2019 ), pp. 21.…”
Section: Discussionmentioning
confidence: 99%
“…Norstedt ( 2019 ) also underlines the paradox that refraining from disclosure to pass as normal possibly only serve to reproduce norms suggesting that the able worker is the ideal one (Norstedt, 2019 ). In our study, one employee associated disclosure with being honest with his supervisor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The invisibility of many episodic disabilities can also result in misperceptions or stigma about a worker's abilities or motivation. Even when a worker discloses an episodic disability, supervisors may be unsure how to initiate conversations about worker performance and accommodations or be concerned about doing more harm than good (Brouwers et al, 2020;Gignac et al, 2012Gignac et al, , 2020Norstedt, 2019;Toth and Dewa, 2014).…”
Section: Introductionmentioning
confidence: 99%